2010
DOI: 10.3138/physio.62.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anterior Tibiofemoral Glides on Knee Extension during Gait in Patients with Decreased Range of Motion after Anterior Cruciate Ligament Reconstruction

Abstract: Purpose: The purpose of this preliminary investigation was to evaluate the effect of anterior tibiofemoral glides on maximal knee extension and selected spatiotemporal characteristics during gait in patients with knee extension deficits after anterior cruciate ligament (ACL) reconstruction. Methods: Twelve patients with knee-extension deficits after recent ACL reconstructions underwent quantitative gait analyses immediately before and after 10 minutes of repeated anterior tibiofemoral glides on the operative l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
2
0
3
Order By: Relevance
“…A reduction in range of motion after ACLR, especially a loss of knee extension at heel strike, 24,46,57 is similarly thought to contribute to development of PFOA by shifting patellar joint reaction forces to regions of trochlear and patellar cartilage that may not be able to adapt to the new loading pattern, initiating a degenerative pathway. 54 Accordingly, in a hop-test study of 45 participants between 1 and 2 years after ACLR, Culvenor et al 14 found that patients with at least partial-thickness cartilage lesions to the patellar or femoral trochlear surfaces by MRI (termed “early PFOA”) demonstrated greater peak knee flexion angle with a trend for greater flexion at first contact than did patients without evidence of early PFOA.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in range of motion after ACLR, especially a loss of knee extension at heel strike, 24,46,57 is similarly thought to contribute to development of PFOA by shifting patellar joint reaction forces to regions of trochlear and patellar cartilage that may not be able to adapt to the new loading pattern, initiating a degenerative pathway. 54 Accordingly, in a hop-test study of 45 participants between 1 and 2 years after ACLR, Culvenor et al 14 found that patients with at least partial-thickness cartilage lesions to the patellar or femoral trochlear surfaces by MRI (termed “early PFOA”) demonstrated greater peak knee flexion angle with a trend for greater flexion at first contact than did patients without evidence of early PFOA.…”
Section: Discussionmentioning
confidence: 99%
“…Post‐operative deficits in knee extension have been shown to be predictive of an increased risk for OA in the ACLR knee . Motion analysis studies have found kinematic changes to the ACLR knee in all three planes, including an increase in knee flexion, a shift towards external tibial rotation, and a shift toward varus rotation . Furthermore, studies of quasi‐static weight‐bearing function after ACL reconstruction have observed a consistent anterior shift in the relative tibial position, even in knees judged to be clinically stable .…”
mentioning
confidence: 99%
“…Eine Einschränkung der Arbeit ist die Größe der Stichprobe. Mit 13 untersuchten Proband(inn)en ist sie zwar klein, allerdings ist sie vergleichbar mit verschiedenen randomisierten kontrollierten Studien, die sich mit der AOT [16][29] [34], mit der Extension des Kniegelenks oder mit der Kniebeweglichkeit nach einer VKB-Plastik [8][30] [35] beschäftigten. Mit dieser Probandenanzahl ist unsere Studie als eine Pilotstudie zu betrachten: Die Ergebnisse sollten zwar vorsichtig bewertet werden, aber dazu ermutigen, in diese Richtung weiter zu forschen.…”
Section: Limitationenunclassified